Insulin resistance and liver histopathology in metabolically unhealthy subjects do not correlate with the hepatic abundance of NLRP3 inflammasome nor circulating IL-1β levels. Issue 1 (3rd May 2021) - Quezada, Nicolas; Valencia, Ilse; Torres, Javiera; Maturana, Gregorio; Cerda, Jaime; Arab, Juan Pablo; Fuentes, Juan José; Pinto, Claudio; Turiel, Dannae; Cortés, Victor
Abstract : Introduction: Systemic chronic low-grade inflammation has been linked to insulin resistance (IR) and non-alcoholic steatohepatitis (NASH). NOD-like receptor protein 3 (NLRP3) inflammasome and its final product, interleukin (IL)-1β, exert detrimental effects on insulin sensitivity and promote liver inflammation in murine models. Evidence linking hepatic NLRP3 inflammasome, systemic IR and NASH has been scarcely explored in humans. Herein, we correlated the hepatic abundance of NLRP3 inflammasome components and IR and NASH in humans. Research design and methods: Metabolically healthy (MH) (n=11) and metabolically unhealthy (MUH) (metabolic syndrome, n=21, and type 2 diabetes, n=14) subjects were recruited. Insulin sensitivity (homeostatic model assessment of IR (HOMA-IR) and Oral Glucose Sensitivity (OGIS120 )), glycemic (glycated hemoglobin), and lipid parameters were determined by standard methods. Plasma cytokines were quantified by Magpix. Hepatic NLRP3 inflammasome components were determined at the mRNA and protein levels by reverse transcription–quantitative PCR and western blot, respectively. Liver damage was assessed by histological analysis (Non-alcoholic Fatty Liver Disease Activity Score (NAS) and Steatosis, Inflammatory Activity, and Fibrosis (SAF) scores). IR and liver histopathology were correlated with NLRP3 inflammasome components as well as with liver and plasma IL-1β levels. Results: Body Mass Index, waist circumference, and arterial hypertension frequency were significantly higher in MUH subjects. These patients also had increased high-sensitivity C reactive protein levels compared with MH subjects. No differences in the plasma levels of IL-1β nor the hepatic content of Nlrp3, apoptosis-associated speck-like ( Asc ), Caspase-1, and IL-1β were detected between MUH and MH individuals. MUH subjects had significantly higher NAS and SAF scores, indicating more severe liver damage. However, histological severity did not correlate with the hepatic content of NLRP3 inflammasome components nor IL-1β levels. Conclusion: Our results suggest that NLRP3 inflammasome activation is linked neither to IR nor to the inflammatory status of the liver in MUH patients.